Sufficientarianism - José Carlos R. Alcantud; Marco Mariotti; Roberto Veneziani (Theoretical Economics, 2022)
Sufficientarianism is a prominent approach to distributive justice in political philosophy and in policy analyses. However, it is virtually absent from the formal normative economics literature. We analyse sufficientarianism axiomatically in the context of the allocation of 0-1 normalised well-being in society. We present three characterisations of the core sufficientarian criterion, which counts the number of agents who attain a “good enough” level of well-being. The main characterisation captures the “hybrid” nature of the criterion, which embodies at the same time a threshold around which the worst off in society is prioritised, and an indifference to equality in other regions. The other two characterisations relate sufficientarianism, respectively, to a liberal principle of non-interference and to a classic Neutrality property.
Keywords: D63; D70; 330; distributive justice; Sufficientarianism